A COMBINED MODEL OF THE DIAPIRIC AND COLLISIONAL FORMATION MECHANISM OF THE PALEOPROTEROZOIC GRANITE-MIGMATITE-GNEISS DOMES OF THE SVECOFENNIAN BELT - O. P. Polyansky; S. K. Baltybaev; A. V. Babichev (Геодинамика и тектонофизика, 2023)
Geological examples of the development of thermal dome structures in the Svecofennian belt demonstrate the relationship between plutonic and metamorphic events and metamorphic strengthening towards the core parts of the structures. The corresponding 2D geological model has been created to make a quantitative assessment of the effect of mantle magmas temperature at the base of the crust and the formation of the diapiric cores surrounded by high-temperature areas with a degree of granulite facies metamorphism. Modeling shows that there is a possibility of melting of the lower crust in the presence of a water fluid under the influence of mantle magmas. After melting, there occurs an ascent of partially molten material towards the upper crustal levels. An absorbed aqueous fluid changes to hydrous melt, thus lowering its viscosity and density. The ascending height of high-temperature cores is determined by the depth of viscous-to-elastoplastic transition in the crustal matter rheology. These materials ascend to upper levels in a partially molten state in the process of overthrusting due to "collisional" tectonics.